Сравнение европейского и российского подходов к профилактике и тактике ведения больных с остеопорозом - Е. И. Кухаж; А. К. Рылова; Е. А. Колесникова; К. А. Лыткина (SINAPS LLC, 2012)
The problem of osteoporosis treatment is very urgent for professionals around the world, but in different countries different strategies are adopted to address this issue. This article presents a comparison of domestic and European approach to the diagnosis and treatment of osteoporosis. Differences in the organization of the process of diagnosis and treatment are available. But on some issues, opinions of experts agree, particularly in Russia and in Europe bisphosphonates recognized as "gold standard" of treatment of osteoporosis. The panelists recognize Foroza® as affordable medicine with high efficacy and safety.